2012
DOI: 10.1007/s00784-012-0721-5
|View full text |Cite
|
Sign up to set email alerts
|

Dental and oral anomalies in incontinentia pigmenti: a systematic review

Abstract: Because of the presence of cleft palate and high arched palate in IP patients, these two anomalies may be considered as diagnostic IP minor criteria as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
1
43
0
4
Order By: Relevance
“…Regarding the increased frequency of high hard palate in our sample (71.4%), in a systematic review conducted in the period between 1993-2012, with 1,286 patients diagnosed with IP, where only 513 provided sufficient information to evaluate possible dental and oral anomalies, aged from 1 year, it was observed that 54.4% had some dental and/or oral anomaly, and high hard palate was one of the most frequent oral abnormalities. Despite the relative small absolute number of palate abnormalities, the number was 25 times higher than that found in general population (16) , indicating that high hard palate may also be a distinctive and useful finding for the diagnosis, as a minor criterion of IP. One advantage is that it is visible since birth, in contrast to dental anomalies that are detectable only after 1 year (16) .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Regarding the increased frequency of high hard palate in our sample (71.4%), in a systematic review conducted in the period between 1993-2012, with 1,286 patients diagnosed with IP, where only 513 provided sufficient information to evaluate possible dental and oral anomalies, aged from 1 year, it was observed that 54.4% had some dental and/or oral anomaly, and high hard palate was one of the most frequent oral abnormalities. Despite the relative small absolute number of palate abnormalities, the number was 25 times higher than that found in general population (16) , indicating that high hard palate may also be a distinctive and useful finding for the diagnosis, as a minor criterion of IP. One advantage is that it is visible since birth, in contrast to dental anomalies that are detectable only after 1 year (16) .…”
Section: Discussionmentioning
confidence: 82%
“…Despite the relative small absolute number of palate abnormalities, the number was 25 times higher than that found in general population (16) , indicating that high hard palate may also be a distinctive and useful finding for the diagnosis, as a minor criterion of IP. One advantage is that it is visible since birth, in contrast to dental anomalies that are detectable only after 1 year (16) . In the evaluation of the stomatognathic system, there was a high prevalence of tongue mobility change (n=6), and oral (n=2) or oronasal breathing (n=1).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, none of these studies had described cases of patients with cleft palate. Moreover, Minic et al 8) conducted a systematic review of dental findings in Bloch-Sulzberger syndrome between 1993 and 2010 and reported a high incidence of dental shape anomalies, hypodontia, and delayed dentition, together with cleft and high-arched palates. Furthermore, approximately 1 in 3 of cases were reported to involve a cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the pigmented spots gradually disappear, and the prognosis is good 11) . Tooth abnormalities include hypodontia, delayed eruption, pegshaped teeth, impacted teeth, morphological anomalies, and malocclusion 6,8) . In addition to reports on skin symptoms associated with this syndrome 11) , a number of studies have also described associated dental features 2,4,6,7,9,13) and corresponding orthodontic treatment 1,3,10,14,16) .…”
Section: Introductionmentioning
confidence: 99%